(untitled) (Plant Tissue Culture and Biotechnology, 2022)
The aim of the present investigation was to develop an efficient and reproducible in vitro regeneration protocol for Brassica campestris L. var. Tori-7. Brassica is one of the most popular and major oil yielding crop plants around the world including Bangladesh. For in vitro regeneration of this crop plant, MS medium supplemented with various concentrations of 6-benzylaminopurine (BAP) and naphthalene acetic acid (NAA) were used. The highest frequency of callus and shoot regeneration was obtained on MS medium supplemented with 3.0 mg/l BAP and 0.2 mg/l NAA from both cotyledonary leaf with petiole and hypocotyl explants. Elongation of shoots was also optimized on the same media composition. For inducing roots from the excised in vitro derived shoots, half strength of MS medium supplemented with 0.3 mg/l indole-3-butyric acid (IBA) was found to be more effective than other hormonal supplements applied. Following the development of effective roots, in vitro raised plantlets were successfully transplanted into soil where they produced flowers and fertile seeds. The plants of R1 generation was successfully established in natural environment. In vitro regeneration protocol of Brassica campestris var. Tori-7 established in this study could be used for future plant genetic transformation experiments. Plant Tissue Cult. & Biotech. 32(2): 237-246, 2022 (December)